Gender Differences in Strategic Behavior in a Triadic Persecution Motor Game Identified Through an Observational Methodology - Pic, Miguel; Navarro-Adelantado, Vicente; Jonsson, Gudberg K. (Frontiers in Psychology, 2020)
The main objective of the work is to address the effective behavior of girls and boys through TMG (Triadic Motor Games). A chasing game ‘The Maze’ was applied, on two class groups with a total of 42 players, 18 girls and 24 boys, who were 12 and 13 year old secondary school students. An observational methodology was applied, with a nomothetic, punctual and multidimensional design. We used a mixed registry system that two expert observers applied later through an observational methodology, obtaining sufficient levels in the quality of the records. THEME was applied to detect temporary regularities, while cross-tabulations and growth trees (CTR model) were applied with the SPSS v.24 tool to reveal whether girls and boys played in a similar or original way. The fact that the specific decision groups (dendograms) within the physical education class are different for girls and boys (p <.005) is worth reflecting. The game’s TMG complexity was addressed through roles-subroles, giving rise to a certain motor asymmetry in relation to gender, which is an expression of behaviors lacking in playful neutrality. On the approach of the mix methods, a study was built using observational methodology that reveals more varied motor solutions in girls, while male behavior showed greater specialization of roles-subroles and linkage of these solutions with the favorable modification of the marker. Identifying relevant variables when they playing TMG (Triadic Motor Games) allows to better know girls and boys by analyzing their relationships while put into practice, sometimes paradoxical.